2016
DOI: 10.1111/cge.12862
|View full text |Cite
|
Sign up to set email alerts
|

The genetic make‐up of ovarian development and function: the focus on the transcription factor FOXL2

Abstract: In a 46 XY individual, the presence of the Y chromosome harboring the testis-determining factor (SRY) triggers testis determination and differentiation. In a 46 XX individual, the absence of SRY and the activation of genes associated with the female pathway lead to ovarian development. The latter process has long been considered as a default pathway. However, recent studies have cast doubts on this dogma. Here, after a brief overview of the main steps of ovarian development, we focus on three genes WNT4, RSPO1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 128 publications
0
29
0
1
Order By: Relevance
“…Forkhead box L2 (FOXL2, OMIM: 605597) is a forkhead transcription factor that contains a fork-head DNA-binding domain and plays a role in ovarian development and function [ 28 , 29 ]. Mutations in FOXL2 are known to cause autosomal dominant POI [ 30 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Forkhead box L2 (FOXL2, OMIM: 605597) is a forkhead transcription factor that contains a fork-head DNA-binding domain and plays a role in ovarian development and function [ 28 , 29 ]. Mutations in FOXL2 are known to cause autosomal dominant POI [ 30 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The forkhead transcription factor FOXL2 has been established as a master gene for folliculogenesis and maintenance of ovarian function in vertebrates [ 45 , 60 ]. Our previous data have shown that FOXL2 transcript and protein are expressed in bovine and ovine endometrium and are regulated by progesterone but not by oestradiol [ 28 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Goat XX fetuses lacking Foxl2 have gonads resembling testes and the induced absence of Foxl2 in adult XX mice results in trans -differentiation of the ovaries into a testis-like gonad. 9 , 10 , 11 In humans, heterozygous loss-of-function FOXL2 mutations are associated with autosomal-dominant blepharophimosis-ptosis-epicanthus inversus syndrome (BPES [MIM: 110100 ]) either with (type I) or without (type 2) ovarian insufficiency as well as ovarian insufficiency without BPES (MIM: 608996 ), but homozygous FOXL2 disruption has not been described. 10 The limited understanding of the genes involved in ovary formation means that for most children with OTDSD/TDSD, the molecular basis is currently unknown.…”
Section: Main Textmentioning
confidence: 99%